PERCEIVED OF RELIGIOUS VALUE: MODEL PEMBENTUK PREFERENSI NASABAH BANK SYARIAH - Amina Sukma Dewi; Anggel Dwi Satria (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2014)
This study aims to examine the influence of perceived of religious value, financial security, profitability, and attractiveness on customer preference in Islamic Bank branch Surakarta.Sampling technique used was purposive sampling. The criterion of participants was respondents who prefer Islamic bank compared to other banks. There were 115 respondents in this resesearch. Methods of data analysis using Generalized Structured Component Analysis (GSCA).The analysis showed that the FIT and AFIT values above 50%, 50 they were 59,1% and 58,3%. While the GFI values above 0.9 which was 0.996. Overall, the research model was fit. Furthermore, analysis of the relationship between variables indicates that there were three hypotheses were supported and one hypothesis was not supported. The hypothesis was supported by the influence of perceive of religious value, profitability, and attractiveness to customers preference. The hypothesis was not supported the effect of financial security to the customer preference.